2019
DOI: 10.3390/cells8111326
|View full text |Cite
|
Sign up to set email alerts
|

Over-Activated Proteasome Mediates Neuroinflammation on Acute Intracerebral Hemorrhage in Rats

Abstract: Background: Neuroinflammation is a hallmark in intracerebral hemorrhage (ICH) that induces secondary brain injury, leading to neuronal cell death. ER stress-triggered apoptosis and proteostasis disruption caused neuroinflammation to play an important role in various neurological disorders. The consequences of ER stress and proteostasis disruption have rarely been studied during the course of ICH development. Methods: ICH was induced by collagenase VII-S intrastriatal infusion. Animals were sacrificed at 0, 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 67 publications
(122 reference statements)
0
25
0
Order By: Relevance
“…Thus, we further explored the mechanism of the interaction between microglia and OLs. Recently, ER stress has attracted much attention for its involvement in many CNS diseases, including amyotrophic lateral sclerosis (ALS), Parkinson's disease and TBI [45]. The ER is a structure in which misfolded and nascent proteins are accurately folded by various chaperones (such as GRP78) before transport by secretory vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we further explored the mechanism of the interaction between microglia and OLs. Recently, ER stress has attracted much attention for its involvement in many CNS diseases, including amyotrophic lateral sclerosis (ALS), Parkinson's disease and TBI [45]. The ER is a structure in which misfolded and nascent proteins are accurately folded by various chaperones (such as GRP78) before transport by secretory vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ER dysfunction caused by protein misfolding and oxidative stress has led to acute central nervous system damage [80,81]. Recently, we have elucidated that acute phase of ICH has exacerbated the ER stress through proteasome overactivation, which also lead to neuroinflammation [82]. Although the studies to describe the relationship between ER stress and ICH are minimal, it is necessary to analyze the role of ER stress in ICH because of the crucial interplay between ER stress and various other factors involved in ICH pathophysiology including microglial activation, oxidative stress, neuroinflammation, and heme release [83][84][85].…”
Section: Crosslinking Er Stress and Ich-related Cell Death Pathwaysmentioning
confidence: 99%
“…Neuroinflammation is a hallmark in ICH that triggered by the endoplasmic reticulum (ER) stress and proteostasis disruption through early degradation of chaperone GRP78 and IkB protein, leading inflammatory response and increased cytokine expression [109]. Interestingly, a study has shown that the receptor of UCN, CRFR1, is involved in CRH-induced neuron apoptosis through the increased GRP78 in a concentration-dependent manner.…”
Section: Urocortin Reduced Pro-inflammatory Cytokine Level In Striatamentioning
confidence: 99%